Effect of regulated deficit irrigation during the vegetative growth period on shoot elongation and oil yield components in olive hedgerows (cv. Arbosana) pruned annually on alternate sides in San Juan, Argentina - Trentacoste, Eduardo Rafael; Calderon Diaz, Facundo Javier; Contreras Zanessi, Octavio Ramiro; Galarza, Walter Antonio; Banco, Adriana Pamela; Puertas, Carlos Marcelo (Springer, 2019)
In super-intensive hedgerows, vegetative vigor must be controlled to allow access to harvesting machinery, particularly under Argentina conditions in which olive trees display excessive vigor. During shoot growth (spring–early summer), flowering and fruit set also take place and the potential yield (bud number) for the following season is defined. The effect of spring–early summer deficit irrigation was studied as a tool to reduce vegetative growth and its influence on inflorescence development, oil yield, and its components. During three seasons in an olive hedgerow (cv. Arbosana), we evaluated a control irrigated at 70% ETc over the season and two regulated deficit treatments irrigated at 50% (RDI-1) and 30% (RDI-2) ETc during the shoot growth period (from August to January) and then 70% ETc until harvest (May). Hedgerows were mechanically topped and pruned annually on alternate sides. We observed that RDI-1 and RDI-2 reduced hedgerow height and width increment after hedging by 15% and 20%, respectively, compared to control. Inflorescence structures were not affected by water deficit, but the control treatment showed on average 5.8 fruits per fruiting inflorescence, significantly higher than 2.4 fruits per fruiting inflorescence observed in RDI-2. After the third season, RDI-1 and RDI-2 were 174% and 146% more productive than control hedgerows, where the pruned sides showed excessive vigor with lower floral bud induction in the following seasons. Fruit size and oil accumulation were also higher in both RDI-1 and RDI-2 than in control, due to greater fruit exposure to irradiance in most deficit treatments. Compared with control, RDI-1 and RDI-2 allowed water savings of 17% and 35%, respectively, but RDI-1 was more productive and had lower alternate bearing than RDI-2.